Calculating the frequency of composite plate and composite spherical shell with different boundary conditions - Adnan Yaseen, Aya; S. Alansari, Luay; Hussain Alnajem, Mohammed; S. Al-anssari, Qusay (International Journal of Engineering and Technology, 2018)
In this work, the Fourier-Ritz approach is used to calculate the natural non- dimensional frequency of composite plate and composite spherical shell with different arrangements of layers (cross and angle ply and symmetrical and anti-symmetrical layers) and different boundary conditions. The Fourier-Ritz approach is the modified Fourier series in connection with a   Ritz technique   to deduce the formulation based on the classical shallow shell theory. Additionally, the Finite Element method (FEM) (ANSYS Software Version 17.2) is used in this work for predicting the natural non- dimensional frequency of composite plate and composite spherical shell. The effect of (b/a) ratio on non- dimensional frequency of composite plate and composite spherical shell is studied for different layers arrangements when the boundary conditions are (CCCC) and (SSSS). The comparisons between the non- dimensional frequency results are made.